2018
DOI: 10.1016/s1470-2045(18)30343-7
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and patient-centred outcomes with olaparib maintenance after chemotherapy in patients with platinum-sensitive, relapsed ovarian cancer and a BRCA1/2 mutation (SOLO2/ENGOT Ov-21): a placebo-controlled, phase 3 randomised trial

Abstract: AstraZeneca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 19 publications
5
94
2
2
Order By: Relevance
“…For example, even though adjuvant sunitinib after resection of high risk renal cell cancer worsened quality of life in the S-TRAC trial, it was reported as “Patients on sunitinib did report increased symptoms and reduced [health related quality of life], but these changes were generally not clinically meaningful, apart from appetite loss and diarrhoea, and were expected in the context of known sunitinib effects.”9 In another example when olaparib did not improve the prespecified primary quality of life analysis in patients with ovarian cancer, this was reported as “not having a significant detrimental effect.”10 Furthermore, many randomised trials of cancer drugs do not report quality of life end points and negative quality of life information is reported less often than positive outcomes 11…”
Section: Better Reportingmentioning
confidence: 99%
“…For example, even though adjuvant sunitinib after resection of high risk renal cell cancer worsened quality of life in the S-TRAC trial, it was reported as “Patients on sunitinib did report increased symptoms and reduced [health related quality of life], but these changes were generally not clinically meaningful, apart from appetite loss and diarrhoea, and were expected in the context of known sunitinib effects.”9 In another example when olaparib did not improve the prespecified primary quality of life analysis in patients with ovarian cancer, this was reported as “not having a significant detrimental effect.”10 Furthermore, many randomised trials of cancer drugs do not report quality of life end points and negative quality of life information is reported less often than positive outcomes 11…”
Section: Better Reportingmentioning
confidence: 99%
“…Efforts are underway to investigate whether patients who do not achieve a response also benefit, because subgroup analyses do demonstrate a benefit in patients who have stable disease and also show evidence of additional antitumor activity in patients who have a partial response after platinum‐based chemotherapy . Careful evaluation of toxicity and quality of life has demonstrated good maintenance of quality of life with all 3 PARP inhibitors and delay or avoidance of symptoms related to recurrence or therapy for recurrence …”
Section: Treatment Of Ovarian Cancer—surgery Systemic Therapy and Rmentioning
confidence: 99%
“…The incidence of MDS, however, is equal to that observed in the placebo groups in the randomized trials of both PARPi and bevacizumab. Quality‐of‐life studies for olaparib and niraparib have shown no decrement in PARPi‐treated women .…”
Section: Efficacy Of Ovarian Cancer Maintenance Therapeutics By Line mentioning
confidence: 99%
“…Lastly, there is a bias against treatments that have yet to demonstrate improvement in OS. Currently available data demonstrate that there is no detriment to quality of life and that OS benefit is desired but not required to declare a treatment effective for ovarian cancer . Furthermore, the PFS2 (time from randomization to progression on next‐line of treatment or death from any cause) data further support a clinical benefit for patients in this setting .…”
Section: Efficacy Of Ovarian Cancer Maintenance Therapeutics By Line mentioning
confidence: 99%